Handbook of mathematical cognition - Campbell, Jamie I. D. (New York : Psychology Press, 2005)
How does the mind represent numbers and make mathematical calculations? What underlies the cognitive development of numerical and mathematical abilities? What factors affect the learning of numerical concepts and procedures? What are the biological bases of number knowledge? Do humans and other animals share similar numerical representations and processes? What underlies numerical and mathematical disabilities and disorders, and what is the prognosis for rehabilitation? These questions are the domain of mathematical cognition, the field of research concerned with the cognitive and neurological processes that underlie numerical and mathematical abilities. Mathematical cognition research intersects a wide array of disciplines including cognitive development, neurological development, computational science, cognitive and educational psychology, animal cognition, cognitive and clinical neuropsychology, neuroscience, and cognitive science. This collection of twenty-seven chapters by leading researchers in the field constitutes a comprehensive review of important facets of mathematical cognition. The volume thereby provides a state-of-the-art general reference for mathematical cognition research, and is intended for academics, scientists, clinicians, and senior students who want a definitive, comprehensive survey of the field.
Part 1: Cognitive Representations for Number and Mathematics. M. Fayol, X. Seron, About Numerical Representations: Insights from Neuropsychological, Experimental and Developmental Studies. M. Brysbaert, Number Recognition in Different Formats. W. Fias, M.H. Fischer, Spatial Representation of Numbers. J. Tzelgov, D. Ganor-Stern, Automaticity in Processing Ordinal Information. M. Zorzi, I. Stoianov, C. Umilta`, Computational Modeling of Numerical Cognition. E.M. Brannon, What Animals Know about Numbers. R. Nún~ez, G. Lakoff, The Cognitive Foundations of Mathematics: The Role of Conceptual Metaphor. Part 2: Learning and Development of Numerical Skills. S. Cordes, R. Gelman, The Young Numerical Mind: When Does It Count? J. Bisanz, J.L. Sherman, C. Rasmussen, E. Ho, Development of Arithmetic Skills and Knowledge in Pre-school Children. K.F. Miller, M. Kelly, X. Zhou, Learning Mathematics in China and the United States: Cross-cultural Insights into the Nature and Course of Pre-school Mathematical Development. M.-P. Noël, L. Rousselle, C. Mussolin, Magnitude Representation in Children: Its Development and Dysfunction. R.S. Siegler, J.L. Booth, Development of Numerical Estimation: A Review. K.C. Fuson, D. Abrahamson, Understanding Ratio and Proportion as an Example of the Apprehending Zone and Conceptual-phase Problem-solving Models. T. Ben-Zeev, S. Duncan, C. Forbes, Stereotypes and Math Performance. Part 3: Learning and Performance Disabilities in Math and Number Processing. D.C. Geary, M.K. Hoard, Learning Disabilities in Arithmetic and Mathematics: Theoretical and Empirical Perspectives. M.M.M. Mazzocco, M. McCloskey, Math Performance in Girls with Turner or Fragile X Syndrome. M.A. Barnes, B. Smith-Chant, S.H. Landry, Number Processing in Neurodevelopmental Disorders: Spina Bifida Myelomeningocele. M.H. Ashcraft, K.S. Ridley, Math Anxiety and its Cognitive Consequences: A Tutorial Review. Part 4: Calculation and Cognition. N.J. Zbrodoff, G,D. Logan, What Everyone Finds: The Problem Size Effect. J.I.D. Campbell, L.J. Epp, Architectures for Arithmetic. J.-A. LeFevre, D. DeStefano, B. Coleman, T. Shanahan, Mathematical Cognition and Working Memory. J.A. Dixon, Mathematical Problem Solving: The Roles of Exemplar, Schema, and Relational Representations. S. Duverne, P. Lemaire, Aging and Mental Arithmetic. M. Pesenti, Calculation Abilities in Expert Calculators. Part 5: Neuropsychology of Number Processing and Calculation. S. Dehaene, M. Piazza, P. Pinel, L. Cohen, Three Parietal Circuits for Number Processing. B. Butterworth, Developmental Dyscalculia. A. Lochy, F. Domahs, M. Delazer, Rehabilitation of Acquired Calculation and Number Processing Disorders
Keywords: podučavanje matematike